2017
DOI: 10.12688/f1000research.11221.1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of novel biologically active natural compounds

Abstract: With the advent of very rapid and cheap genome analyses and the linkage of these plus microbial metabolomics to potential compound structures came the realization that there was an immense sea of novel agents to be mined and tested. In addition, it is now recognized that there is significant microbial involvement in many natural products isolated from “nominally non-microbial sources”. This short review covers the current screening methods that have evolved and one might even be tempted to say “devolved” in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 92 publications
0
25
0
1
Order By: Relevance
“…In the past few decades, the discovery and development model of bioactive natural products has changed from the determination of phytochemistry of plants to the use of advanced analytical techniques, genomics, and metabolomics combined with high‐throughput and high‐content screening (Newman, ). Metabolomics as a rapid screening method provides an efficacious way to discover bioactive ingredients from herbal medicines.…”
Section: Metabolomics: An Overviewmentioning
confidence: 99%
“…In the past few decades, the discovery and development model of bioactive natural products has changed from the determination of phytochemistry of plants to the use of advanced analytical techniques, genomics, and metabolomics combined with high‐throughput and high‐content screening (Newman, ). Metabolomics as a rapid screening method provides an efficacious way to discover bioactive ingredients from herbal medicines.…”
Section: Metabolomics: An Overviewmentioning
confidence: 99%
“…The first screen covered isolated metabolites from marine sponges (Jaspis splendens) to prove that the overall system could function. The following screen then utilized a 500-plus pure compound set from the Nature Bank collection at Griffith University [1,4,29,30]. The results demonstrated that such a HCS produced multiple possibilities for the identification of the interaction(s) with cellular organelles/protein interactions, being limited only by the specificity of the fluorescent probes used to demonstrate the responses.…”
Section: Application Examples Of Hcs In Natural Product Researchmentioning
confidence: 99%
“…Reasons for this fact are related to the lack of expertise and infrastructure for biological screening, high costs as well as time consuming if samples must be sent to overseas laboratories. It is therefore highly desirable to develop in-house bioassays in institutes for chemical research which are inexpensive, rapid and do not require the chemists a specialized knowledge of biology or pharmacology [1][2][3]. The bioassay laboratories at Vietnam Academy of Science and Technology (VAST) had therefore initially established the "bench-top" bioassays since the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in the genome sequencing technology, it was revealed that microorganisms still represent an essential source for novel natural products that need to be explored [ 19 ]. For example, the genome information of two well-studied species, Streptomyces coelicolor A3(2) [ 3 ] and Streptomyces avermitilis [ 20 ], revealed the presence of several cryptic biosynthetic gene clusters (BGCs), thereby highlighting their potential to produce new metabolites in addition to the existing ones from these organisms [ 21 ].…”
Section: Introductionmentioning
confidence: 99%